Le notti di Copacabana - Jacobbi, Ruggero (Moderna/Comparata, 2018)
Thanks to Gioia Benedetti's careful philological work, a short, narrative and hitherto unknown text brings back the voice of one of the most original and brilliant Italian critics of the 20th century. After the trip to Brazil in his youth, in his single finished novel set in Rio de Janeiro in the Fifties, Notti di Copacabana, Ruggero Jacobbi conveyed not only the climate and atmosphere of a distant and in some ways mythical world such as Brazil, but also a significant track of the readings, meetings and influences of the great texts of Portuguese and South American literature, at the time mostly unknown in Italy. Jacobbi had an extraordinary talent at catching and interpreting the changes in the narrative code, and in this book, the author offers an incredibly intriguing experimental story with alternating voices and characters and intertwining events, contributing to the creation of a suspenseful atmosphere.